ALGORITHM DEVELOPMENT FOR BREAK-EVEN ANALYSIS OF UNMANNED AERIAL VEHICLE - Muhammad Ridlo Erdata Nasution; Dhaesa Pramana (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2019)
Break-Even Analysis is an important step to be considered in the design process of a product. In order to facilitate this cost analysis in the framework of unmanned aerial vehicle design, a numerical algorithm is proposed and implemented on an in-house software. The developed algorithm adopts the cost components of Modified DAPCA IV Cost Model. It aims to calculate the number of units to achieve Break-Even Point and its corresponding unit price, as well as the obtained profit margin. Three example cases are employed in the assessment of the outcomes of the proposed algorithm, whereby reasonable results and good agreements with theoretical trends are concluded.